1997
DOI: 10.1165/ajrcmb.17.5.2866
|View full text |Cite
|
Sign up to set email alerts
|

Airway Eosinophils, T Cells, Th2-Type Cytokine mRNA, and Hyperreactivity in Response to Aerosol Challenge of Allergic Mice with Previously Established Pulmonary Inflammation

Abstract: Asthma is characterized by acute episodes of nonspecific airway hyperreactivity and chronic pulmonary inflammation exacerbated by stimuli including allergen exposure. In order to reproduce the physiologic and immunologic responses that occur in asthmatic patients, we have characterized a model of antigen-induced inflammation in which allergic mice (B6D2F1) that had been challenged once with aerosolized ovalbumin and had developed a pulmonary cellular infiltrate were rechallenged 1 wk later. Pulmonary inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Considering the high expression of Thy-1 on murine TCs [29], [14] and the pathogenic role of TCs in OVA-induced lung inflammation [21], we excluded that the reduced lung inflammation in Thy-1 À/À mice was dependent of the different Thy-1 expression levels on TCs. In Thy-1 BM chimera, the Thy-1-expression was detectable on 70% of TCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the high expression of Thy-1 on murine TCs [29], [14] and the pathogenic role of TCs in OVA-induced lung inflammation [21], we excluded that the reduced lung inflammation in Thy-1 À/À mice was dependent of the different Thy-1 expression levels on TCs. In Thy-1 BM chimera, the Thy-1-expression was detectable on 70% of TCs.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high expression of Thy-1 on murine TCs and the pathogenic role of TCs in OVA-induced lung inflammation [20,21], we tested whether the differences observed in Thy-1 À/À mice, compared to WT mice, were merely due to the lack of Thy-1 on TCs. Because Thy-1 is expressed only by TCs and not by other haematopoietic cells, we focused on the expression of Thy-1 on TCs.…”
Section: Tcs Are Not Involved In Decreased Influx Of Inflammatory Celmentioning
confidence: 99%
“…It has recently been reported that in mice primarily sensitized with OVA and subsequently challenged with the same Ag through the airways, a reexposure to OVA 1 wk after the first airway challenge results in an augmented allergic response (41). Although various factors could contribute to the augmented response, considering our finding that IgE persists in the airways for Ͼ2 wk after last Ag exposure, it is possible that IgE immune complexes, which are formed in the airways when the mice are reexposed to the Ag, contribute to the potentiated secondary response.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary eosinophilia in response to OVA was generated in mice as described previously (25,26). In this experience we modified this model.…”
Section: Induction Of Murine Asthma Modelmentioning
confidence: 99%